2005
DOI: 10.1002/nme.1430
|View full text |Cite
|
Sign up to set email alerts
|

A quadratically convergent unstructured remeshing strategy for shape optimization

Abstract: SUMMARYA novel unstructured remeshing environment for gradient-based shape optimization using triangular finite elements is presented. The remeshing algorithm is based on a truss structure analogy; in solving for the equilibrium position of the truss system, the quadratically convergent Newton's method is used. Exact analytical sensitivity information is therefore made available to the shape optimization algorithm. The overall computational efficiency in gradient-based shape optimization is very high.In solvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…Our mesh generator solves for the equilibrium position of a truss structure , which doubles as the FE mesh, using the ideal element length field h{k}MathClass-punc,kMathClass-rel=1MathClass-punc,2MathClass-punc,3MathClass-punc,MathClass-op… as the unloaded truss lengths, as opposed to directly optimizing the mesh according to some optimality criterion . It has been demonstrated that this approach generates ‘good’ meshes.…”
Section: Adaptive Mesh Generatormentioning
confidence: 99%
See 2 more Smart Citations
“…Our mesh generator solves for the equilibrium position of a truss structure , which doubles as the FE mesh, using the ideal element length field h{k}MathClass-punc,kMathClass-rel=1MathClass-punc,2MathClass-punc,3MathClass-punc,MathClass-op… as the unloaded truss lengths, as opposed to directly optimizing the mesh according to some optimality criterion . It has been demonstrated that this approach generates ‘good’ meshes.…”
Section: Adaptive Mesh Generatormentioning
confidence: 99%
“…We start with an initial uniform mesh at k = 0, using a uniform ideal element length field h {0} . After each analysis, we compute the ideal element length field trueh̆{k} using the refinement strategy described in Section 4.1.…”
Section: Adaptive Mesh Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…For the material properties we use Young's modulus E = 200GPa and Poisson's ratio ν = 0.3. The meshes required for the finite element analyses are generated using a quadratic convergent remeshing strategy [24] with ideal element length h 0 = 1mm. To illustrate the discontinuous nature of the objective function, the two control variables x 8 and x 9 are perturbed around the reference configuration depicted in …”
Section: Multivariate Example Problem: Shape Optimizationmentioning
confidence: 99%
“…For this, design element concept (Imam, 1982), 0020-7683/$ -see front matter Ó 2010 Elsevier Ltd. All rights reserved. doi:10.1016/j.ijsolstr.2010.03.004 adaptive meshing (Bennet and Botkin, 1984) and remeshing (Wilke et al, 2006) techniques were used. A comprehensive review of the early development of shape optimization can be found in the survey literatures (Braibant and Fleury, 1984;Haftka and Grandhi, 1986;Ding, 1986;Hsu, 1994).…”
Section: Introductionmentioning
confidence: 99%